Honey, I shrunk the extracellular space: Measurements and mechanisms of astrocyte swelling. Issue 11 (30th May 2022) - Walch, Erin; Fiacco, Todd A.
Abstract: Astrocyte volume fluctuation is a physiological phenomenon tied closely to the activation of neural circuits. Identification of underlying mechanisms has been challenging due in part to use of a wide range of experimental approaches that vary between research groups. Here, we first review the many methods that have been used to measure astrocyte volume changes directly or indirectly. While the field has recently shifted towards volume analysis using fluorescence microscopy to record cell volume changes directly, established metrics corresponding to extracellular space dynamics have also yielded valuable insights. We then turn to analysis of mechanisms of astrocyte swelling derived from many studies, with a focus on volume changes tied to increases in extracellular potassium concentration ([K + ]o ). The diverse methods that have been utilized to generate the external [K + ]o environment highlight multiple scenarios of astrocyte swelling mediated by different mechanisms. Classical potassium buffering theories are tempered by many recent studies that point to different swelling pathways optimized at particular [K + ]o and that depend on local/transient versus more sustained increases in [K + ]o . Main Points: Many methods have been used to measure or estimate astrocyte volume change. Physiological astrocyte volume changes are driven by fluctuations in extracellular K + . Underlying mechanisms may vary as a function of [K + ]o and transient/local versus sustained K + elevations.